Adsorption of Metal Ion Manganese (Mn) in Sodium Silicate Solution using Chitosan. Issue 1 (May 2021) - Febriana, E; Pitriani, P; Handayani, M; Irawan, J; Prasetyo, A B; Sulistiyono, E; Firdiyono, F; Hendrawati,
Abstract: High purity Silica precipitate is very potential materials which can be utilized for many applications for high grade silicon, filler, photovoltaic, catalytic chemical, etc. Indonesia has abundant natural resources including quartz sand as raw materials for making high purity silica precipitate. Silica precipitate is made by roasting quartz sand forming sodium silicate solution. In order to obtain high purity silica precipitate, purification of sodium silicate solution is needed. In this study, purification of sodium silicate solution is performed by adsorption process of metal ion manganese (Mn) using chitosan as adsorbent. The experiment was done using batch technique. The variation of adsorption process was performed to get optimum conditions such as sample concentration, adsorbent mass, contact time, pH and temperature. The adsorption of metal ions of Mn was analyzed by atomic adsorption spectroscopy. The result of experiment shows that the best mass of chitosan for Mn adsorption process is 0.2 grams which gives percentage adsorption of 56.63%. The optimum contact time is 30 minutes, it results percentage adsorption of 52.5%. The optimum pH 3 gives adsorption percentage of 58.67%. And the best temperature for adsorption is at 60 °C with the percentage adsorption of 65.72%. Adsorption mechanism of metal ion Mn follow the isotherm model of langmuir and freundlich with the linearity value of R 2 = 0.99 and 0.98 respectively.